Assessing the viability of carbamoylethyl pullulan-g-stearic acid based smart polymeric micelles for tumor targeting of raloxifene. (2nd December 2021) - Sethi, Sheshank; Bhatia, Sachin; Kamboj, Sunil; Singh, Ram Sarup; Rana, Vikas
Abstract: The present investigation entails the synthesis of smart pullulan polymeric micelles for evaluating its tumor targeting potential. For this purpose, two step polymerization synthesis reactions were conducted. In the first step, carbamoylethylation occurs by reaction of the free alcoholic moieties at 6th position of glucopyranose unit of pullulan with acrylamide in presence of alkali to obtain carbamoylethyl pullulan (CmP). In the second step, CmP undergoes graft polymerization with stearic acid (SA) to obtain CmP-g-stearic acid diblock co-polymer (CmP-g-SA) as evident from FTIR and NMR analysis. The XpRD spectra showed crystalline nature that was further confirmed by SEM indicating rough and poly-porous morphology. The QbD based optimized formulations of raloxifene HCl (RLX) loaded polymeric micelles (RLX PMs) exhibited pH-dependent release profile with added advantage of 1.2 times reduction in percentage hemolysis giving substantial compatibility with erythrocytes. In vivo pharmacokinetic performance of RLX PMs suggested enhanced mean residence time and volume of distribution. Besides, the biodistribution study of RLX PMs manifested enhanced entry of RLX in mammary carcinoma tissues as compared to normal tissues suggested that CmP-g-SA based micelles enhanced the anti-tumor activity of RLX. Overall, the findings pointed toward the biocompatibility of CmP-g-SA as a potential carrier system for the delivery of RLX.